Efektivitas Beberapa Media Perbanyakan dan Dosis Aplikasi Trichoderma SP Terhadap Pertumbuhan Selada Keriting (Lactuca Sativa) - Nabila Buana Kania; Harwanto; M Saikhu (PT ADRIANI MANDIRI PUBLISHER, 2026)
This research aims to determine the effectiveness of various propagation media and application doses of Trichoderma sp. on the growth of curly lettuce. The study employs a Factorial Randomized Block Design (RBD) with two factors: propagation media as the first factor and application doses as the second factor. There are 9 treatments: (M1D1 = corn at 25g dose), (M1D2 = corn at 50g dose), (M1D3 = corn at 75g dose), (M2D1 = bran at 25g dose), (M2D2 = bran at 50g dose), (M2D3 = bran at 75g dose), (M3D1 = pellets at 25g dose), (M3D2 = pellets at 50g dose), and (M3D3 = pellets at 75g dose), each with 3 replications. Observations included plant height (cm), number of leaves (leaves), root length (cm), and wet weight (g). The results showed that the 25g dose of bran media produced the best plants in terms of plant height, number of leaves, and wet weight parameters. Meanwhile, the 50g dose of bran media produced the best plants in terms of root length.